Detection of measles cases in the Republic of Guinea in 2017–2018 - I. N. Lavrentieva (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
In 2017, WHO reported 596 confirmed measles cases in Guinea Republic connected to the 2016–2017 epidemic outbreak that was stopped after additional immunization (SIA) against measles in two provinces of the country. Improving the effectiveness of SIA is associated with the identification of epidemiologically significant groups of the population. The aim of the study was to analyze 2017–2018 measles cases and assess population immunity to measles virus in the Republic of Guinea. Materials and methods. A total of 810 blood serum samples collected from patients with maculo-papular rash and clinical diagnosis “measles?” were tested for measles virus-specific IgM-and IgG antibody level. 445 sera of conditionally healthy individuals aged 7 months to 67 years were examined for anti-measles virus IgG antibody level. Immunoglobulins of classes M and G were detected by ELISA with test systems «Anti-Measles Virus ELISA (IgM)» (Euro immun, Germany) and «Anti-Measles Virus ELISA (IgG)» (Euroimmun, Germany). Results and discussion.In 2017–2018, the epidemic process of the measles in the Republic of Guinea proceeded very intensively, being markedly prevalent in children among age groups. In 2018, more than half of the cases (61.6%) were identified in children aged 1 to 5 years old; the second most abundant age group was children under one year (18.6%), probably due to violated measles vaccination, which in GR are subject to children of nine months of age. It was found that 16.4% of patients (60 out of 366) had documented data on measles vaccination. Potentially, high proportion of measles cases among pre-vaccinated subjects was due to insufficient immune response to a single immunization in children of 9 months of age. Moreover, lowered vaccine-related properties might also be violated “cold chain” during vaccine transportation occurring in tropical climate. Analyzing 445 subjects revealed that total number of measles virus seronegative subjects was 8.3%. However, the vast majority of them were children and young adults aged 7 months to 22 years, where 52.4% of seronegative subjects were identified. Thus, the data obtained indicate that intensive measles virus circulation in human population was continued that necessitate interventions for improving epidemiological surveillance, extend routine measles vaccination coverage and conduct SIAs against measles in GR.